Trends in the prevalences of congenital anomalies and age at motherhood in a southern European region: a population-based study. Issue 3 (3rd March 2014) - Cambra, K; Ibañez, B; Urzelai, D; Portillo, I; Montoya, I; Esnaola, S; Cirarda, F B
Abstract : Objectives: To estimate the prevalences of the main groups of congenital anomalies and to assess their trend over time. Design: Population-based study of prevalences. Setting: The Basque Country, Spain. Participants: All births and all congenital anomalies diagnosed prenatally, at birth or during the first year of age, in all hospitals of the country, from 1999 to 2008. Main outcomes measures: Total diagnosed prevalences and prevalences at birth of all chromosomal and non-chromosomal anomalies, Down's syndrome, anomalies of the nervous system, urinary, limbs, digestive system and congenital heart defects. Results: Mean age (SD) of women at childbirth and the proportion of them over 35 years of age shifted from 32.1 (4.5) years, with 18.3% in 1999–2001, to 32.3 (4.7) years, with 23.9% in 2006–2008. Between 1999 and 2008, 991 cases of chromosomal anomalies and 3090 of non-chromosomal anomalies were diagnosed, which yields, respectively, total prevalences of 5.2‰ and of 16.2‰. Among chromosomal anomalies, Down's syndrome is the most frequent (2.9‰). With marginal statistical significance, the results point at an increasing trend in total diagnosed chromosomal anomalies, but a decreasing one in prevalences at birth. Among non-chromosomal congenital anomalies, congenital heart defects are the most frequent (5.2‰) one. Rates of all non-chromosomal, urinary and limb anomalies grew during the study period, whereas those of congenital heart defects and anomalies of the digestive system did not change significantly. Conclusions: In the Basque Country, rates of chromosomal anomalies are higher than the overall estimated prevalence in European countries, and continue to increase slightly, which may be related to the rise in maternal age. Rates of non-chromosomal anomalies are within the European frequent range of values, and the increases observed need to be checked in the following years.